Evaluation of Developments in the Mortgage Market in Relation to the Covid-19 Pandemic in the Czech Republic - Linda Pudilová; Lucie Severová (Communications of International Proceedings, 2021)
Over the last 15 years, the number of approved mortgage loans in the Czech Republic has increased by more than 1,5 %. Mortgage loans clearly dominate the market for home loan products. The Czech mortgage market has seen a number of substantial changes in the last 3 years. In 2018, the Czech National Bank adopted several regulatory measures designed to reduce the level of mortgage risk, thereby limiting the risk that banks are exposed to when granting mortgage loans to low-income homebuyers. Subsequent measures, which began to be implemented in 2020 with a view to bolstering the economy during the Covid-19 pandemic, have resulted in easing somewhat the rules on loan approval. Despite the instituted measures, the number of provided home loans and mortgages can be said to follow a stable growing trend over the long term. The presented article aims to analyze the Czech mortgage market and to predict the future direction of home loans using time series and regression analyses. Consideration is also given to the analysis of the impacts exerted by monetary measures adjusting the discount rates on the Czech mortgage market.
Keywords: Covid-19; Debt; Financing; Installment; Interest; Mortgage